2021
DOI: 10.3390/su132112244
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Heavy Metals Pollution and Ecological Risk in Sediments of Mediterranean Sea Drain Estuaries in Egypt and Phytoremediation Potential of Two Emergent Plants

Abstract: Environmental pollution and its eco-toxicological impacts have become a large and interesting concern worldwide as a result of fast urbanization, population expansion, sewage discharge, and heavy industrial development. Nine heavy metals (Pb, Cd, Fe, Mn, Zn, Ni, Cu, Cr, and Co) were evaluated in 20 sediment samples from the estuaries of four major drains along the Mediterranean shoreline (Nile Delta coast) to determine the possible ecological effect of high heavy metal concentrations as well as roots and shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
(78 reference statements)
1
5
0
Order By: Relevance
“…Generally, the investigated metals can be sorted in descending order as follows: Fe > Mn > Zn > Ni > Co > Cu > Pb > Cd. The results support previous studies that found that the metals were arranged in similar order and at similar concentrations (dry weight) in most studied locations (Abdel Ghani et al, 2013 ; El-Amier et al, 2021 ; El-Metwally et al, 2021 ; El-Sorogy et al, 2016 ; Redwan & Elhaddad, 2020 , 2022 ; N. F. Soliman et al, 2015 ).
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…Generally, the investigated metals can be sorted in descending order as follows: Fe > Mn > Zn > Ni > Co > Cu > Pb > Cd. The results support previous studies that found that the metals were arranged in similar order and at similar concentrations (dry weight) in most studied locations (Abdel Ghani et al, 2013 ; El-Amier et al, 2021 ; El-Metwally et al, 2021 ; El-Sorogy et al, 2016 ; Redwan & Elhaddad, 2020 , 2022 ; N. F. Soliman et al, 2015 ).
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…The use of indices based on metal concentrations to assess the potential risks for humans and environment is well documented [29][30][31][32][33]. However, their use in assessing the success of remediation trials is very poorly documented, with most of the studies limited to assessing the risks and identifying the phytoremediation potential of plant species [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal accumulation in river sediments originating from industry and mining activities has been a serious issue in developing countries including Rwanda and especially due to the toxicity effects of the metals mentioned [1]. The river sediments tend to accumulate heavy metals and other organic pollutants and therefore the sediment quality serves to be a good indicator of water pollution [2].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are natural constituents of rivers' sediments. Nevertheless, they become a problem when they go beyond the standards of being safe mostly due to their toxic effects on human beings, plants, and different animals [1]. The World Health Organization reported 143,000 deaths and 600,000 new cases of child intellectual disabilities [10], 3,000 people have diseases resulting from heavy metals concentration, and 600 of them died in Japan [11].…”
Section: Introductionmentioning
confidence: 99%